2009
DOI: 10.1186/1471-2199-10-91
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple 9-mer-based protein binding microarray with DsRed fusion protein

Abstract: Background: The interaction between a transcription factor and DNA motif (cis-acting element) is an important regulatory step in gene regulation. Comprehensive genome-wide methods have been developed to characterize protein-DNA interactions. Recently, the universal protein binding microarray (PBM) was introduced to determine if a DNA motif interacts with proteins in a genome-wide manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Protein DNA-binding properties are traditionally investigated by methods such as EMSAs and filter-binding assays (Garner and Revzin, 1981;Sö derman and Reichard, 1986). The development of the Q9 protein-binding microarray along with the availability of whole-genome sequence information and advances in microarray technology have greatly facilitated our ability to characterize protein DNA-binding specificities in vitro (Kim et al, 2009). The results of Q9 protein-binding microarray analysis and EMSA demonstrated that StMYB1R-1 binds DNA mainly at G / A GATAA sequences ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein DNA-binding properties are traditionally investigated by methods such as EMSAs and filter-binding assays (Garner and Revzin, 1981;Sö derman and Reichard, 1986). The development of the Q9 protein-binding microarray along with the availability of whole-genome sequence information and advances in microarray technology have greatly facilitated our ability to characterize protein DNA-binding specificities in vitro (Kim et al, 2009). The results of Q9 protein-binding microarray analysis and EMSA demonstrated that StMYB1R-1 binds DNA mainly at G / A GATAA sequences ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The quadruple 9-mer (Q9) protein-binding array was developed as a screening tool for rapid identification of DNA-binding sequences of TFs and contains more than 100,000 unique double-stranded DNA oligomers synthesized as quadruples of all possible 9-mer combinations (Kim et al, 2009). Using a DsRed fusion protein of StMYB1R-1 (StMYB1R-1:DsRed) to monitor binding, Q9 proteinbinding microarray analysis yielded 1,028 putative DNA-binding sequences (.3,500 relative signal intensity).…”
Section: Stmyb1r-1 Functions As a Tfmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the DNA-binding sequence specificity of At-MYB44 by a comprehensive genome-wide method, using a universal PBM (Kim et al, 2009). The PBM was designed to contain quadruples of all possible 9-mer combinations, permitting unequivocal interpretation of the cis-acting elements.…”
Section: Discussionmentioning
confidence: 99%
“…Using the full-length cDNA of AtMYB44 (TAIR clone 119B8), proteins fused at the N-termini with DsRed fluorescent protein and a polyhistidine-tag were expressed in the Escherichia coli strain BL21-ColonPLus, as described previously (Kim et al, 2009). A protein-binding mixture containing 200 nM fusion protein was incubated with the quadruple 9-mer PBM (Q9-PBM) at 25°C for 1 h. Fluorescence images were obtained with a 4000B microarray scanner (Molecular Devices, USA).…”
Section: Protein Binding Microarray (Pbm) Analysismentioning
confidence: 99%